Indian missionaries in the land of gold. - Thakur, Upendra (Patna Kashi Prasad Jayaswal Research Institute, 1986)
On the Hindu and Buddhist civilization in Southeastern Asia.
Keywords: Hinduism -- Missions -- Southeast Asia. Buddhism -- Missions -- Southeast Asia. Missions, Indic -- Southeast Asia. Hinduism -- history. Buddhism -- history. Religious Missions -- history. Buddhism -- Missions. Hinduism -- Missions. Missions, Indic. Southeast Asia. Buddhismus. Mission. Hinduismus. Südostasien.